The golden spike how a photograph celebrated the transcontinental railroad - Nardo, Don 1947- (North Mankato, Minnesota Compass Point Books, 2015)
"Chronicles the historic meeting of two railroad lines in 1869 that linked the U.S. transcontinental railroad and Andrew J. Russell's famous photograph of the event"--
Historic connection -- Immense undertaking -- Uniting the republic -- A changing country
History
Includes bibliographical references and index
1 2 13
Keywords: Pacific railroads -- History -- Juvenile literature; Railroads -- United States -- History -- Juvenile literature; Railroads -- West (U.S.) -- History -- Juvenile literature